Ali : the life of Ali Bacher - Hartman, Rodney (Johannesburgo (South Africa) : Penguin Viking, 2004)
Ali Bacher, b. 1942, former cricketer and managing director of the United Cricket Board of South Africa.
Includes index.
Keywords: Bacher, Ali, -- 1942-; Cricket managers -- South Africa -- Biography; Cricket -- South Africa